Effect of Pilates Method on 6-10-Year-Old Dancesport Dancers' Physiological Responses - Gerda Tumonytė; Roma Aleksandravičienė; Kristina Zaičenkovienė (Lithuanian Sports University, 2018)
Background. Dancesport dancers were investigated aiming at improving their physical qualities, posture, balance, ﬂexibility and endurance. Undoubtedly, the Pilates method is one of the best ways for exercising one's core muscles and ﬂexibility. However, there is a lack of data in the academic literature concerning the inﬂuence of Pilates exercises on dancers' ftness levels depending on diﬀerent age groups and ranking. Based on this, the aim of our study was to evaluate the 16-week Pilates exercise eﬀects on 6-10-year-old Dancesport dancers' physiological responses. Methods. The static deep trunk muscle endurance was tested with pressure measuring device "Stabilizer", ﬂexibility was assessed using "Sit and Reach" test, static balance - "Flamingo" test and dynamic balance - "Star" excursion test. Research participants were Dancesport dancers (n = 38) who had been practising Pilates (13 girls and 7 boys) and attending a usual dance program (11 girls and 7 boys). Results. After 16 weeks, dancers who had been practicing Pilates method signifcantly improved static and dynamic deep trunk muscle endurance in all positions, static and dynamic balance and ﬂexibility. The dancers that practiced a usual dance program signifcantly improved static deep muscle endurance only in the prone position, dynamic in the supine position, but their dynamic balance, static balance and ﬂexibility did not change signifcantly. Conclusion. Better improvement in 6-10-year-old Dancesport dancers of deep trunk muscle endurance, balance and ﬂexibility was found after 16 weeks of Pilates exercises compared to dancers who practised a usual dance program. Keywords: Pilates method, Dancesport dancers, deep muscular endurance, balance, ﬂexibility.